History of the prevention of mother-to-child transmission of HIV in Thailand - Nittaya Phanuphak; Praphan Phanuphak (Elsevier, 2016)
Strategies for the prevention of mother-to-child transmission (PMTCT) of HIV have undergone considerable evolution based on scientific evidence, both at global and local levels. Because of the rapid expansion of the HIV epidemic among the heterosexual population, and the relatively advanced mother and child health infrastructure, Thailand has been the site of international study for more efficacious and cost-effective PMTCT regimens since mid-1990. The example of the Thai Red Cross Society in providing standard PMTCT care through public donations under the patronage of Her Royal Highness Princess Soamsawali is an example that non-governmental organisations in other countries can follow to accelerate access to standard PMTCT care. However, there are still many challenges before vertical transmission of HIV is completely eradicated.